A research on the cadmium ions adsorption of Sulfhydryl- and sulfo-functionalized UIO-66 with silica layer from water. Issue 1 (February 2021) - Liu, Jianming; Cui, Haohui; Li, Jianhua; Chen, Meichen
Graphical abstract: Highlights: Two modified materials UIO-66@mSi-SH and UIO-66@mSi-SO3 H were synthesized successfully. UIO-66@mSi-SH and UIO-66@mSi-SO3 H have good adsorption and regeneration capabilities. Cadmium removal efficiency is best when the initial pH = 7. Adsorption was correlated with Sulfhydryl- and sulfo- functional groups on the UIO-66. Abstract: In this study, adsorption behavior on UIO-66, UIO-66@mSi-SH and UIO-66@mSi-SO3 H were investigated with a great emphasis on cadmium. The UIO-66@mSi-SH was synthesized by postsynthetic modification with silica layer, and sulfo-functionalized UIO-66 with silica layer (UIO-66@mSi-SO3 H) was obtained from oxidizing UIO-66@mSi-SH with H2 O2 . All prepared adsorbents were characterized by FT-IR, SEM, XRD and BET. The BET value of UIO-66 can reach 1304.59 m 2 g −1 . To fit the adsorption behavior curve of Cd 2+, the isothermal adsorption curve (Langmuir, Freundlich and D-R models) and kinetic model (Quasi first-order kinetic, Quasi second-order kinetic and Elovich model) were utilized. It shows that the basic mechanism of adsorption process was determined by R 2, AIC and other constants and the adsorption performance is shown as UIO-66@mSi-SO3 H > UIO-66@mSi-SH > UIO-66. Langmuir and Elovich models showed better fitting results of UIO-66@mSi-SO3 H adsorption process for Cd 2+, and the R 2 values were 0.97471 and 0.97817 respectively. The theoretical maximum adsorption capacity of UIO-66@mSi-SO3 H for Cd 2+ is 409.96 mg g -1 by Langmuir isothermal adsorption. The UIO-66@mSi-SO3 H shows great adsorption capacity for Cd 2+ with a surface area of 126.728 m 2 g −1 and a pore volume of 0.102 cm 3 g −1, which is approximately 93.73 % higher than UIO-66. Besides, more than 90 % adsorbents was able to be regenerated in shorter time after 5 cycles.